Simulating the effect of haze management using system dynamics: a case study of Beijing - Lv, Furong; Lu, Yunjing; Tang, Haiping (Frontiers in Environmental Science, 2024)
Haze is a pollution phenomenon that has become increasingly frequent in recent years, primarily composed of SO2, NOx, and particulate matter. Since the "PM2.5 Crisis" in 2013, the Beijing-Tianjin-Hebei region has been plagued by haze. After a series of high-intensity management activities, the air quality in Beijing has continued to improve. To investigate the effectiveness of the haze control measures in Beijing, a dynamic management model was constructed using the system dynamics approach and implemented using Stella software. The model is simulated and evaluated the contribution to different governance strategies (increasing investment in science and technology innovation, reducing motor vehicle ownership, reducing coal consumption, and a combination policy) to reduce haze in Beijing from 2010-2025. The validity and robustness of the model were verified through model testing and validation. The simulation results showed that: (1) the combination policy has the most significant effect on reducing energy consumption and pollution emissions, which would reduce energy consumption by 38.93 million tons and pollution emissions by 128.33 thousand tons in 2025, (2) among the single treatment measures,reducing industrial coal consumption is the most effective measure to reducing haze, (3) it is necessary to strengthen the joint prevention and control of the Beijing-Tianjin-Hebei region in the future to promote the sustainable development of the regional environment.